Phylogenomic analysis of gastroenteritis-associated Clostridium perfringens in England and Wales over a 7-year period indicates distribution of clonal toxigenic strains in multiple outbreaks and extensive involvement of enterotoxin-encoding (CPE) plasmids. Issue 10 (25th September 2019) - Kiu, Raymond; Caim, Shabhonam; Painset, Anais; Pickard, Derek; Swift, Craig; Dougan, Gordon; Mather, Alison E.; Amar, Corinne; Hall, Lindsay J.
Abstract : Clostridium perfringens is a major enteric pathogen known to cause gastroenteritis in human adults. Although major outbreak cases are frequently reported, only limited whole-genome sequencing (WGS) based studies have been performed to understand the genomic epidemiology and virulence gene content of outbreak-associated C. perfringens strains. We performed phylogenomic analysis on 109 C . perfringens isolates (human and food) obtained from disease cases in England and Wales between 2011 and 2017. Initial findings highlighted the enhanced discriminatory power of WGS in profiling outbreak C. perfringens strains, when compared to the current Public Health England referencing laboratory technique of fluorescent amplified fragment length polymorphism analysis. Further analysis identified that isogenic C. perfringens strains were associated with nine distinct care-home-associated outbreaks over the course of a 5-year interval, indicating a potential common source linked to these outbreaks or transmission over time and space. As expected, the enterotoxin cpe gene was encoded in all but 4 isolates (96.3 %; 105/109), with virulence plasmids encoding cpe (particularly pCPF5603 and pCPF4969 plasmids) extensively distributed (82.6 %; 90/109). Genes encoding accessory virulence factors, such as beta-2 toxin, were commonly detected (46.7 %; 51/109), and genes encoding phage proteins were also frequently identified. Overall, this large-scale genomic study of gastroenteritis-associated C. perfringens suggested that three major cpe -encoding (toxinotype F) genotypes underlie these outbreaks: strains carrying (1) pCPF5603 plasmid, (2) pCPF4969 plasmid and (3) chromosomal- cpe strains. Our findings substantially expanded our knowledge on type F C. perfringens involved in human-associated gastroenteritis, with further studies required to fully probe the dissemination and regional reservoirs of this enteric pathogen, which may help devise effective prevention strategies to reduce the food-poisoning disease burden in vulnerable patients, such as the elderly.